Evaluation methods to determine soil and water conservation status in different ecosystems (Bangladesh Journal of Botany, 2025)
In order to study the effect of different vegetation types on ecosystem water and soil conservation function, an area was selected as the research object, and the evaluation method of ecosystem water and soil conservation function under the application of different plant measures was designed based on ENVI and ArcGIS software. Delineate five types of vegetation in the study area. The experimental results showed that in the evaluation of water conservation function, the water conservation capacity of the five types of vegetation and the water conservation amount per unit area are ranked from large to small, i.e. grassland, shrub grassland, woodland, woodland and shrub mixed areas, cultivated land, in the evaluation of soil water conservation function, the potential and actual soil erosion of cultivated land are much greater than those of the other four vegetation types. Among the remaining four vegetation types, shrubs > mixed area of shrubs and forest land > forest land > grassland. In the order of soil conservation per unit area, cultivated land is far less than other vegetation types, and the other orders are grassland > forest land > mixed area of forest land and shrub > shrub. It can be seen that among the five vegetation types, grassland has the strongest effect on soil and water conservation, and cultivated land is the worst.Bangladesh J. Bot. 54(3): 797-804, 2025 (September) Special